THE RELATIONSHIP BETWEEN KNOWLEDGE AND PRODUCTION HEALTH BEHAVIOR IN ELEMENTARY SCHOOL CHILDREN IN BLABAK 1, KEDIRI REGENCY - Mia Ashari Kurniasari; candra Dewinataningtyas; ellatyas rahmawati tejo putri; dwi margaretta andini (UNIVERSITAS AIRLANGGA, 2023)
Introduction: The transition from childhood to adolescence or puberty is a time when hormonal development can affect the physical and psychological development of an early adolescence. The change can be a traumatic experience, if there is no early preparation. Knowledge is very necessary and can be a major factor in shaping one's actions or behavior, because at this time the importance of knowledge about adolescent physical changes, because at this time there is a lot of pressure with physical, biological changes and pressure on environmental changes, while elementary school children are still rarely exposed to reproductive health knowledge. The purpose of this study was to analyze the relationship between reproductive health knowledge and behavior in elementary school children. The method used is observational analytics with a sample number of 75 musing total sampling smapling techniques, analysis tests used using chi squere. The results showed that the low knowledge of respondents with poor reproductive health behavior was around 26.7%. High knowledge of respondents with good reproductive health behavior is around 21.3%. Poor reproductive health behavior with low knowledge is 18.7%, while for good reproductive health behavior with good knowledge is around 33.3%. The results of the chi-square test obtained a value of p = 0.001, it can be interpreted that H0 is rejected and Ha is accepted, there is a relationship between knowledge and reproductive health behavior in children of SD Blabak 1. Conclusion: There is a relationship between knowledge and reproductive behavior in elementary school children 1 Blabak Kediri.